Methods of Social Control in Educational Institutions between Legal Rules and Social Values: A Field Study on a Sample of Basic Education Teachers in the Municipality of Zliten - Akhkhil, Fatima Ali; Mubarak, Bashir Muftah (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The school is in the intended educational institution it works on education in an organized and planned manner, as it contributes to the upbringing of the new generation, and preparing them for life. The legal rules and social values prevail in the school and society. Therefore, society was entitled to methods of educational social control between legal rules and social values. The study aimed to identify the methods of social control in educational institutions, as well as the most important rules and laws regulating social control in educational institutions. the study was based on the analytical descriptive approach using the comprehensive pool method. the study was applied to a sample of basic education teachers in the municipality of Zliten, in my school (Abdul Rahman ibn Auf, and Umm Salamah), and their number was (50) teachers, and they were chosen through a random sample. This study relied on a questionnaire as a data collection tool, then was analyzed using the SPSS statistical program. The study found that the methods of social control, the rules and laws regulating social control, and the social values associated with social control in educational institutions came to a very high degree. The most important method of social control in educational institutions is (the school encourages students to promote positive behaviors financially and morally. The school uses classroom discipline laws for reform and not as a means of punishment. It imposes severe penalties on students who violate the legal rules within the legal rules within the school. The school contributes to the establishment of cultural competitions organized by teachers to consolidate the concept of positive discipline and develop team spirit). The most important values represented social control associated with social control in educational institutions were (the teacher modifies the erroneous social behaviors prevalent in the community, and the teacher accepts the students, opinions about the legal rules within the school. The school motivates students to promote positive behaviors financially and morally. The school uses classroom discipline laws for reform and not as a means of punishment, and severe penalties are imposed). The most important rules and laws regulating social control in educational institutions were (wrong social and prevailing in society, and the teacher accepts the opinions of students about the legal rules within the school. The school motivates students to promote positive behaviors financially and morally. The school uses classroom control laws for reform and not as a means of punishment and imposes strict penalties on students who violate the legal rules within the school the school contributes to the establishment of cultural competitions organized by teachers to consolidate the concept of positive control and develop team spirit). The most important social values associated with social control in educational institutions were (the teacher maintains a balance between social values and seeks to instill the values of faith in God Almighty and the Sunnah of His Prophet. The school promotes the customs, traditions, and social values prevailing in the school community, and develops faith in the values and ideals of the Arab nation).
Keywords: Methods; Social control; Legal rules; Social values